Pemberdayaan Masyarakat Dalam Upaya Pemanfaatan Sampah Plastik Untuk Meningkatkan Pendapatan (Studi Pada Pokda Di Desa Ujung Piring, Bangkalan) - Hananah Hananah; Mochammad Isa Anshori (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
The problem in this study is that the community's awareness and concern for handling waste by the people of Ujung Piring village is still very lacking, the habit of burning garbage is still increasing greatly, in the community at the tip of the plate in dealing with existing waste problems. Besides that, by burning garbage, it is felt by the community to be the fastest way to deal with this problem, but this is actually not the case. Research describes community empowerment in increasing community income with POKDA by collecting plastic waste from the community, depositors and from other management operations, turning the value of goods higher, these activities create job opportunities and additional income for the community. The method used in this research is descriptive qualitative method. Data collection was carried out through observation, in-depth interviews, and documentation. The results showed that the research activities explaining Community Empowerment in Plastic Waste Efforts to Increase Income at POKDA in Ujung Piring Village, Bangkalan were able to make significant changes to the environment.